2004
DOI: 10.1007/s11661-004-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Some studies on the thermal-expansion behavior of c-fiber, SiC p , and in-situ Mg2Si-Reinforced AZ31 Mg alloy-Based hybrid composites

Abstract: Magnesium alloy-based hybrid composites with carbon-fiber, SiC p , and in-situ Mg 2 Si reinforcements have been prepared by the squeeze-infiltration technique. The results of the studies done on the measurement of the coefficient of thermal expansion after thermal cycling of these composites show that the thermal cycling initially leads to rapid linear expansion of the composite. However, the expansion becomes stabilized after a few cycles, pointing toward formation of the stable interfaces due to the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, Mg 2 Si compound is prone to form as undesirable coarse Chinese script particles under low solidification rates, which are detrimental to mechanical properties. It has also been reported that the presence of the Mg 2 Si particles with a Chinese-script morphology in Mg-based composites may not be conducive for providing thermal stability, while it is expected that the massive type of Mg 2 Si helps to provide thermal stability, due to its globular shape [10,11]. Therefore, it is of interest to refine the morphology of the coarse Mg 2 Si particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mg 2 Si compound is prone to form as undesirable coarse Chinese script particles under low solidification rates, which are detrimental to mechanical properties. It has also been reported that the presence of the Mg 2 Si particles with a Chinese-script morphology in Mg-based composites may not be conducive for providing thermal stability, while it is expected that the massive type of Mg 2 Si helps to provide thermal stability, due to its globular shape [10,11]. Therefore, it is of interest to refine the morphology of the coarse Mg 2 Si particles.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Poor high-temperature strength and lower elastic modulus are two issues related to magnesium and their alloys that limit their application. [11,12] Although there are several studies on Mg alloy development to overcome these persistent problems, more work is needed in this direction to enhance the strengthening process in the system.…”
Section: Introductionmentioning
confidence: 99%